Digitally Actions Leading to Sexual Abuse: Cyber Grooming - Fırat, Sunay (The Bulletin of Legal Medicine, 2023)
The effect of computer technology, especially with the development of the internet, on sexual abuse against children has become more evident. For this reason, the threats we experience in daily life have also started to take place in the virtual environment with their own versions. In this study, the definition, risk factors, characteristics, process, protection and prevention methods of cybergrooming which is an area of violence in digital environment will be discussed. Cyber grooming means communicating with a child, virtually or in real life, over internet for the purpose of sexually abusing them. In this process, groomer aims to serve to strengthen the child’s sexually abusive behaviours. Therefore, as the style of cyber butlerization often reflects the personality and behavioural pattern of both the abuser and the victim, the duration and intensity of this process varies considerably. Thus, by its very nature, cyber grooming involves a form of manipulation. It is a traumatic process that has a serious negative impact on the victim, where communication is initiated in first stage, then methods such as buying gifts, giving money, praising, isolating child from his/her environment, and trying to arrange a personal appointment with the victim are used to deceive and blackmail the child. As a result, the inclusion of the concept of cyber grooming in Turkish Criminal Code in our country will make it possible to criminalize the preparatory actions that will potentially lead to the sexual abuse of children, and children will be protected from all kinds of sexual abuse.
Keywords: Child abuse, cyber grooming, online sexual abuse, internet